Hacia una nueva visión de la política social en América Latina: desmontando mitos - Kliksberg, Bernardo (Sociedad y Economía, 2002)
This paper deals with the social situation that prevails in Latin America. First, a picture is made of the delicate social problems of the region: poverty, unemployment, the situation of the children, health, the blocking of social mobility, the degradation of the family, insecurity and inequality. Second, a description and a criticism is made of the myths that have been constructed and spread regarding the social policy, and an effort is made to show some of the regressive impacts that these myths do have upon the efficacy of the policy. Third, as a conclusion, attention is called upon the need for “emergency ethics” that moves to immediate action in front of a situation that does not tolerate any more procrastination.